Addressing Health and Well-Being Through State Policy: Understanding Barriers and Opportunities for Policy-Making to Prevent Adverse Childhood Experiences (ACEs) in South Carolina. Issue 2 (February 2020) - Srivastav, Aditi; Spencer, Mindi; Thrasher, James F.; Strompolis, Melissa; Crouch, Elizabeth; Davis, Rachel E.
Purpose: As adverse childhood experiences (ACEs) become increasingly recognized as a root cause of unhealthy behaviors, researchers, practitioners, and legislators seek to understand policy strategies to prevent and mitigate its effects. Given the high prevalence of ACEs, policies that address ACEs can meaningfully prevent disease in adulthood and improve population health. We sought to understand barriers and opportunities for policies to prevent and mitigate ACEs by exploring state legislator perspectives. Setting and Participants: Twenty-four current state legislators in South Carolina. Design: In 2018, we conducted semistructured interviews with 24 state legislators. Participants were recruited using maximum variation sampling. The researchers individually analyzed each interview transcript using focused coding qualitative techniques. A high inter-rater agreement was demonstrated (κ = .76 to .87), and discrepancies were resolved through discussion. Method: The data collection and analysis were guided by Multiple Streams Theory, which identifies 3 key components (attention to the problem, decisions about policy options, and the impact of political landscape) that can lead windows of opportunity for passing policies. Results: Legislators identified several factors that can influence the passage of legislation on ACEs: awareness of ACEs; gaps in understanding about what can be done about ACEs; the use of data and stories that contextualize the problem of ACEs; capitalizing on the bipartisanship of children's issues; and linking to current ACEs-related issues on the policy agenda, such as school safety and violence prevention and the opioid epidemic. Conclusion: Public health researchers and practitioners should focus on the factors identified to advocate for policies that prevent ACEs and/or address their health consequences.